KERAGAMAN KONSEP KEPEMIMPINAN DALAM ORGANISASI - HAFULYON HAFULYON (IAIN Batusangkar, 2016)
Quick effloresce leadership diversity along with changed it organization. Elements included leadership key as locomotive reach organization aim. For ala boss success conventional necessary approachings amongst those character approaching, behaviour and situasional. Meanwhile leadership in Islamic uses terminology umara orulil amri and khadimul ummah . That leadership diversity gets to be seen of severally variable inspire leadership amongst those autocratic, democratic, laissez faire That diversity its practice can at k ombinasikan in move subordinate in organisational, including confound that diversity is deep Islamic leadership concept via severally approaching amongst those keteladanan’s approaching, integrity , and deliberation (democratic) to reach to the effect organization.Key words: Keragaman, kepemimpinan, organisasi